2021
DOI: 10.3390/polym13183034
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical and Thermal Properties of Poly(ethylene-co-vinyl acetate) (PECoVA) Composites with Pristine Dolomite and Organophilic Microcrystalline Dolomite (OMCD)

Abstract: Poly (ethylene-co-vinyl acetate) (PECoVA) composite containing organophilic microcrystalline dolomite (OMCD) was studied to replace the non-recyclable silicone elastomer in biomedical application. Pristine dolomite (DOL) is an inorganic mineral filler and is hydrophilic in nature, hence incompatible with most polymers and limits its use in biomedical applications. DOL was subjected to a combination of size reduction, tip sonication and a surface modification process to obtain a more effective dolomite filler, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…due to their direct contact with the human body, polymers utilized in biomedical applications must exhibit biocompatibility and non-toxicity. Additionally, they should meet specific essential requirements, such as comfort and protection of human tissues [1,2]. uhMWPe polymers have been found to be beneficial in biomedical applications due to its biocompatibility, durability, toughness and high wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…due to their direct contact with the human body, polymers utilized in biomedical applications must exhibit biocompatibility and non-toxicity. Additionally, they should meet specific essential requirements, such as comfort and protection of human tissues [1,2]. uhMWPe polymers have been found to be beneficial in biomedical applications due to its biocompatibility, durability, toughness and high wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the use of 5% MMT as a filler can improve the mechanical and thermal barrier properties of Nylon 6, and similarly, the addition of nano-calcium-carbonate and nanoclay to high-density polyethylene (HDPE) can significantly increase the modulus of elasticity [55,56]. Also, dolomite as filler was able to improve the mechanical and thermal properties of various polymeric materials [57,58].…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, dolomite is known as "Batu Reput". This natural mineral rock can be abundantly found in Perlis, the northwestern part of Peninsular Malaysia [3]. Perlis's dolomite is an alkaline earth oxide with a primary composition of CaMg(CO3)2 and minor impurities such as ferrite and silica.…”
Section: Introductionmentioning
confidence: 99%
“…Perlis's dolomite is an alkaline earth oxide with a primary composition of CaMg(CO3)2 and minor impurities such as ferrite and silica. It also contains magnesium ore that is only active when calcined at temperatures above 850°C and under atmospheric pressure [3]. Due to its low cost, abundancy and non-toxicity, the use of dolomite as mineral filler in polymer composite is starting to increase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation